Tandem synthesis of pyrroloisoquinolines through 5-endo iodolactamization, oxidative functionalization and α-amidoalkylation reaction. Issue 25 (24th June 2015) - Tang, Yu; Han, Ranran; Lv, Mingcan; Chen, Yang; Yang, Pan
Abstract: Pyrroloisoquinolines formation through 5- endo halocyclization of unsaturated amides, direct C–H oxidative functionalization and N -acyliminium cyclization is described. A range of β-iodo-pyrrolidinones can be efficiently synthesized using this method, making it an excellent approach for constructing natural products containing pyrrolidinones. Besides, we have developed convenient alternative routes for the synthesis of pyrroloisoquinolines in two separated steps or one pot. Graphical abstract: